Analisis Avability Infrastruktur Jaringan VOIP di Universitas Sahid Surakarta - Susilo, Dahlan; Saputro Al Haris, Firdhaus Hari; Wahono, Ari (Gaung Informatika, 2011)
VoIP is a technology that utilizes the Internet Protocol to provide voice communications electronically and in real-time. How it works to change the voice into digital data format that can be transmitted through a specific IP network. Conducted research methodology, consisting of six strands include observational studies and interviews, literature study, analysis and system design, experiment, test the quality of the system, and conclusions. VoIP works on a computer network installed VoIP server. The server acts as a proxy that has the benefits of inter-user communication. VoIP communications can be carried out within the scope of the campus and outside the campus with an internet connection. The test results with the method of random sampling McCall using several factors related to the operational properties of software, it can be concluded that the quality of VoIP in Sahid University of Surakarta was 76.5% with good results.